Polyhydroxyalkanoates: waste glycerol upgrade into electrospun fibrous scaffolds for stem cells culture - Canadas, Raphael Faustino (2014)
This integrated study shows that waste glycerol can be bio-valorized by the fabrication of electrospun scaffolds for stem cells. Human mesenchymal stem cells (hMSC) provide an interesting model of regenerating cells because of their ability to differentiate into osteo-, chrondro-, adipo- and myogenic lineages. Moreover, hMSC have modulatory properties with potential on treatment of immunologic diseases. Electrospun fiber meshes offer tunable mechanical and physical properties that can mimic the structure of the native extracellular matrix, the natural environment where cells inhabit. Following a biorefinery approach, crude glycerol directly recovered from a biodiesel post-reaction stream was fed as major C source toCupriavidus necator DSM 545 to produce polyhydroxyalkanoates at polymer titers of 9â 25 g/L. Two of the P(3HB-4HB-3HV) terpolymers produced, one containing 11.4% 4HB and 3.5% 3HV and the other containing 35.6% 4HB and 3.4% 3HV, were electrospun into fibers of average diameters of 600 and 1400 nm, respectively. hMSC were cultured for 7 days in both fiber meshes, showing their ability to support stem cell growth at acceptable proliferation levels. Comparative results clearly demonstrate that scaffold topology is critical, with electrospun PHA fibers succeeding on the support of significant cell adhesion and proliferation, where planar PHA films failed.